Monetary Policy and Its Role in Economic Development: Iraq as a Model - Lateef, Thawra (International Journal of Psychosocial Rehabilitation, 2020)
Monetary policy is an important macroeconomic policy that plays an important and effective role in regulating the money supply and controlling cash liquidity and credit. Through this important role, monetary authorities represented by the central bank as the highest monetary authority can achieve specific vital goals according to priorities which determined by the problem that the economy suffers from. The monetary policy in Iraq has not witnessed a significant improvement in its required role, as this is due to the difficult conditions that Iraq has gone through at the political and economic levels. It has contributed to weakening its role in achieving economic stability in Iraq. However, the change of the political system in April 2003 and the ensuing years and the Central Bank's obtaining independence under the Law 56 of 2004 made monetary policy an important tool in influencing the Iraqi economy in a new way that is completely different from the previous, thus the central bank was able to adopt this policy to reach to the economic goals which have an important role in influencing the economy and then the society. It is important to mention that monetary policy is an important and effective policy in achieving economic development which cannot be overlooked in setting the required economic plan, as this does not mean that it has the full capacity to do so because it is part of the overall the collective economic policies that work to achieve the goal that the economic policy planners and seek in the country, as it is the economic stability, so this needs an economic vision and philosophy in which monetary policy plays a major role.